2001
DOI: 10.1210/me.15.4.565
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Induces Specific Interaction between Insulin Receptor and Protein Kinase C  in Primary Cultured Skeletal Muscle

Abstract: Certain protein kinase C (PKC) isoforms, in particular PKCs beta II, delta, and zeta, are activated by insulin stimulation. In primary cultures of skeletal muscle, PKCs beta II and zeta, but not PKC delta, are activated via a phosphatidylinositol 3-kinase (PI3K)-dependent pathway. The purpose of this study was to investigate the possibility that PKC delta may be activated upstream of PI3K by direct interaction with insulin receptor (IR). Experiments were done on primary cultures of newborn rat skeletal muscle,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 0 publications
7
45
0
Order By: Relevance
“…This association, upstream in insulin signal transduction, is consistent with the suggested role for PKC␦ in regulating the function of IR itself (25,26). Our results, showing that an important component of the ability of TNF-␣ to interfere with IR signaling involves disturbance of the insulin-induced physical association between PKC␦ and IR/IRS-1, further strengthen this idea.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This association, upstream in insulin signal transduction, is consistent with the suggested role for PKC␦ in regulating the function of IR itself (25,26). Our results, showing that an important component of the ability of TNF-␣ to interfere with IR signaling involves disturbance of the insulin-induced physical association between PKC␦ and IR/IRS-1, further strengthen this idea.…”
Section: Discussionsupporting
confidence: 89%
“…In preliminary studies, we found that cultured mouse skeletal muscle cells express PKC isoforms ␣, ␤2, ␦, ε, , and , in agreement with other studies on mammalian skeletal muscle in vivo and in culture (15,38 -40). In a recent study on rat skeletal muscle in primary culture, we showed that insulin induces a rapid and specific physical association between IR and PKC␦ and that this physical linkage is essential for the continuation of the IR signaling cascade (26). We therefore reasoned that interference of PKC interactions with upstream elements might be involved in TNF-␣ effects on IR signaling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, overexpression of WTPKCδ in the primary skeletal muscle cells increased GLUT4 translocation and glucose uptake in the absence of insulin stimulation. In another study, it was reported that insulin induces PKCδ to associate directly with IR and that this isoform plays an essential role in insulin-induced tyrosine phosphorylation and internalization of IR [13]. In all of these and subsequent studies on skeletal muscle cells, interaction of IR occurred exclusively with PKCδ and not with any other PKC isoform (α, βII, ε or ς).…”
Section: Novel Pkc Isoforms Pkcδmentioning
confidence: 94%
“…Activation of these elements may then lead to stimulation of additional enzymes, among which are certain members of the protein kinase C (PKC) family of serine-threonine kinases. Recent studies implicate specific PKC isoforms in the insulin-signaling cascade [2][3][4][5][6][7][8][9][10][11][12][13][14]. Insulin activates PKCs α, βII, δ and ζ in several cell types including cell lines of skeletal muscle [11,12,15].…”
Section: Introductionmentioning
confidence: 99%